Climate change effects on ski tourism - Béki, Piroska (Applied Studies in Agribusiness and Commerce, 2017)
Nowadays, climate change poses a common recurring problem in our everyday life. The weather forecasts tend to be inaccurate, the swiftly changing weather often makes fun of the people. The same unpredictability applies for forecasting the amount of precipitation or snowing. The major problem in ski tourism consists in the gradual shift of seasons, namely there is no snow in December yet, while at Easter-time we can count on such an enormous amount of snow. I’d like to present this climate condition and offer a sort of way out of this problem. In my empirical study, I have carried out document-analysis along the data collection phase, and I made half-structured deep-interviews, as well.My research questions were the following: How is the winter season affected by climate change or by the lack of snow? Due to the unreliable climatic conditions what is the estimated ratio of drop in tourism in the season? How much shorter is a skiing-season and how does it affect the operation of the local ski-school? What are the features of pre, and post peak-season tourists’ emergence? How and for how long can a smaller ski-resort be maintained? What is the biggest challenge, problem at the ski-resorts along the state border?First of all, I’d like to present and tackle the various solutions emerged facing the challenges of climate change effects related to skiing, on the other hand, I have made some personal interviews with Hungarian ski instructors working abroad and also with managers of Austrian ski schools trying to find out the various answers and reactions they have hammered out coping with the new challenges and difficulties in ski tourism.Hungary can not be considered a skiing nation, although more and more people tend to take up skiing and get involved in this special field of sport tourism. The number of ski slopes being built and developed is increasing, yet the Hungarians ski-lovers tend to visit rather the foreign sport centers for the time being. The reasons mostly involve the various length and versatile difficulty level of the ski slopes. We should also take into account the challenging conditions imposed by climate change on the smaller winter sport centers and the way they can cope with it and also compete with other sport centers with similar features.Climate change affects considerably the operation of skiing season, and the service providers must adapt to the new conditions. Many resort venues struggle for survival, though most of the local self-governments are clearly aware of the importance of ski-tourism, particularly in Austria.